Impact of electricity theft on power quality - Arango, L. G.; Deccache, E.; Bonatto, B. D.; Arango, H.; Ribeiro, P. F.; Silveira, P. M. (2016 17th International Conference on Harmonics and Quality of Power (ICHQP), 2016)
Electricity theft is responsible for economic problems for the electric utility due to revenue loss caused by electricity consumers that are not paying for it. The stealer has a tendency to consume more energy, resulting also in power quality problems. An increase in power demand to values greater than the transformer rated power can result in different quality deviations, like transformer overload, voltage unbalance and steady state voltage drop on system buses. The objective of this paper is to analyze, by using MatLab simulations and considering different grid configurations, how electricity theft results in power quality issues, specifically voltage drop in steady state. Additionally, it is shown how the steady state voltage drop can result in economic penalties for the electric utility when the proper voltage exceeds the network operational standards.